The evolution of Canada's global export market share - Daniel De Munnik; Jocelyn Jacob; Wesley Sze (Bank of Canada, 2012)
Following gains during the 1990s, Canada's global market share of goods exports has declined markedly in recent years. In this regard, the constant market share analysis framework is used to decompose changes in Canada's global market share into competitiveness and structural effects over the 1990 - 2010 period, as well as to draw some comparisons to a number of other countries. While Canadian firms have been facing competitiveness challenges in recent years resulting from the persistent strength of the Canadian dollar and poor productivity performance relative to major trade competitors, other factors such as to whom Canada sells its products and the product it sells, have also significantly affected the performance of Canadian exports. Over the past decade, the structure of the geographic market to which Canada exports, with a large weight on the relatively slow-growing U.S. market, and a small weight on other economies, particularly the relatively fast-growing emerging market economies, has exerted the majority of the overall net negative impact on Canadian exports.
Keywords: F10; F14; F43; 330; Balance of payments and components; Exchange rates; International topics